MAKNA SIMBOLIK UBORAMPE RITUAL PEMAKAMAN JENAZAH DI DESA PAGOTAN KABUPATEN MADIUN DAN POTENSINYASEBAGAI SUMBER PEMBELAJARAN IPAS SD/MI - Azzahra, Balqis Nahdliya; Hanif, Muhammad; Parji, Parji (Wewarah: Jurnal Pendidikan Multidisipliner, 2023)
The community in Pagotan Village, Geger District, Madiun Regency still adheres to traditional ceremonies, one of which is maintaining the use of uborampe in funeral rituals for corpses. This research aims to find out the symbolic meaning of Uborampe in funeral rituals for corpses in Pagotan Village, whether it can be a source of elementary/MI learning. This research uses a qualitative approach, namely (field research). The type of data obtained was analyzed using the interactive data analysis technique of the Miles and Huberman data model. The results of this research explain that the Pagotan Village Community carries out traditional and religious burial rituals for corpses. The burial of corpses in Pagotan Village uses uborampe in the form of ambengan pepak, sego golong, tumpeng mungkur, jenang baro-baro, tukonan market, ingkung, ngatepi, kapok, godong kelor, kembang roncean, sawur, kendi, umbrella, kendi, gloggor, young coconut , pandhoso, tombstone. Symbolic meanings have the potential to be a source of SD/MI science and science learning in learning outcomes for students to recognize cultural diversity, local wisdom, history in the province where they live and connect them with the current context of life. Masyarakat di Desa Pagotan Kecamatan Geger Kabupaten Madiun masih berpegang teguh dengan upacara adat istiadat, salah satunya mempertahankan penggunaan uborampe dalam ritual pemakamanjenazah.Penelitian ini bertujuan untuk mengetahui Makna Simbolik Uborampe Dalam Ritual Pemakaman Jenazah Di Desa Pagotan apakah dapat menjadi sumber pembelajaran SD/MI.Penelitian ini menggunakan pendekatan kualitatif  yakni (field Research). Jenis Data yang diperoleh dianalisis dengan teknik analisa data interaktif model data Miles and Huberman. Hasil penelitian ini menjelaskan bahwa Masyarakat Desa Pagotan melakukan ritual pemakaman jenazah secara adat dan agama. Pelaksanaan pemakaman jenazah di Desa Pagotan menggunakan uborampe berupa ambengan pepak, sego golong, tumpeng mungkur, jenang baro-baro, tukonan pasar, ingkung, ngatepi, kapuk, godong kelor, kembang roncean, sawur, kendi, payung, kendi, gloggor, kelapa muda, pandhoso, batu nisan. Makna simbolik berpotensi sebagai sumber pembelajaran IPAS SD/MI pada Capaian Pembelajaran peserta didik mengenal keberagaman budaya, kearifan lokal, sejarah di profinsi tempat tinggalnya serta menghubungkan dengan konteks kehidupan saat ini.